Retratos de uma adolescente grávida: desamparo, violência sexual e vulnerabilidade - Hayeck, Marcelo (2022)
The phenomenon of sexual violence is a recurring theme in the media, mobilizing devastating affections and opinions, especially when it comes to sexual violence committed against children or adolescents with a result of pregnancy. The pregnancy of a fetus originated in rape is a political and governmental theme crossed by different fields of knowledge, but it lacks scientific productions to give voice to the suffering of young people. The objective of this research was to build a clinical case whose lecture allows analyzing the effects of sexual violence in vulnerable adolescence under the logic of psychic helplessness in dialogue with sociopolitical impasses. The methodology used was as follows: Psychoanalysis served as a theory, method of investigation and form of individual treatment of a fourteen-year-old black teenager, victim of intrafamily sexual violence with a result of pregnancy, who wanted to become the baby's mother. The construction of the clinical case made it possible to identify forms of vulnerability and violence experienced by the adolescent in her family and social circuit. The analysis of the case allowed us to think about how psychic helplessness was actualized in situations in which the total lack of guarantees paralyzed the young woman in a position of submission to the other and removed her from her right to tell her truth. Without authorization and power to speak for themselves, there is a discursive helplessness that limits the teenager in the stigma of "liar", but the organization of the public service and the writing of this academic work manage to give a voice to the young woman - giving her full right to voice. Parallel to the helplessness, the writing of the case allowed us to think about how violence and vulnerabilities cause a mutation in the social bond, promoting a regime of unrestricted submission rather than a way of existing permeated by care, protection and pleasures arising from the field of the Other [l’Autre].